FT-Raman signatures of genomic DNA from plant tissues. Issue 2 (2009) - Muntean Muntean, Cristina M. Cristina M.; Halmagyi Halmagyi, Adela Adela; Puia Puia, Mircea D. Mircea D.; Pavel Pavel, Ioana Ioana
Abstract : The vibrational spectra of eight genomic DNAs from leaf tissues (sword fern ( Nephrolepis exaltata L.), chrysanthemum ( Dendranthema grandiflora Ramat.), redwood ( Sequoia sempervirens D. Don. Endl.), orchids ( Cymbidium × hybrida ), common sundew ( Drosera rotundifolia L.), potato ( Solanum tuberosum L.) and scopolia ( Scopolia carniolica Jacq.)) have been analyzed using FT-Raman spectroscopy, in the wavenumber range 500–1800 cm –1 . FT-Raman signatures, spectroscopic assignments and structural interpretations for these plant genomic DNAs are reported. Spectral differences among two genomic DNAs, independently extracted from chrysanthemum leaves, are to be observed between 1000–1200 cm –1 . Besides, similarities in the FT-Raman spectra of genomic DNAs from potato and scopolia leaves, respectively, have been found. This might be explained by their belonging to the same family (Solanaceae). Other spectral differences among genomic plant DNAs have also been observed. These findings demonstrate that Raman spectroscopy may be exploited to distinguish different plant genomic DNAs. The present study provides a basis for future use of Raman spectroscopy to analyze specific plant DNA–ligand interactions or DNA structural changes induced by plants' stress conditions associated with their natural environment.